Exploring the Effectiveness of Pre-Exposure Prophylaxis (PrEP) Use for HIV Prevention among High-Risk Populations - Dave , Pallav (Asian Journal of Pharmaceutical Research and Development, 2024)
Addressing the global burden of HIV requires effective preventative measures that have been shown to have high efficacy rates. PrEP is one of the preventative measures that is effective in preventing HIV. Different clinical trials and population studies have shown PrEPto have an efficacy rate of 40% to 90% when it comes to preventing HIV. Due to its high efficacy, PrEPcan reduce new HIV infections populations considered to be high risk. However, for efficacy to be high, there is a need to increase medication adherence and address the existing barriers that limit uptake. Some of these barriers are lack of knowledge, inadequate access, stigma,lack of trust in service providers, low perception of HIV risk, cost, and fear of side effects. Addressing these barriers can increase PrEP uptake and help in reducing HIV’s risk among high-risk populations. Some of the measures that can be put in place to address these barriers are providing education and training, allocating enough resources, leveraging technology, lowering PrEP costs, increasing insurance coverage, and improving communication among the targeted population.